Ventilator-associated events: prevalence and mortality in Japan - Nakahashi, Susumu; Imai, Hiroshi; Imanaka, Hideaki; Ohshimo, Shinichiro; Satou, Tomoko; Shima, Masanori; Yanagisawa, Masami; Yamashita, Chizuru; Ogura, Toru; Yamada, Tomomi; Shime, Nobuaki; Japanese Society of Intensive Care Medicine (JSICM), for the VAEs Review Committee in the (Journal of Thoracic Disease, 2018)
Background: In 2013, the Centers for Disease Control and Prevention (CDC) issued the concept of the ventilator-associated events (VAEs) as a quality indicator (QI) in the intensive care unit (ICU). A number of studies have been conducted in the United States and other Western countries to evaluate its practicality. However, information on VAEs in non-Western countries is scarce. The purpose of this preliminary study was to illuminate the incidence and associated mortality rate of VAEs in Japan, as a first step in the effort to determine its practicality. Methods: We conducted a multi-center, retrospective review of patient medical record using VAEs surveillance algorithm. We analyzed 785 patients with ≥2 days of mechanical ventilator (MV), admitted to the ICU at seven urban hospital in Japan. The prevalence of VAEs, including its three subtypes, and in-ICU mortality were researched. Results: Forty-nine VAEs were identified, affecting 5.7% of patients requiring MV for ≥2 days and 6.4 per 1,000 MV days. Mortality in those who developed VAEs was 42.9%, significantly higher than the rest of the cohort (vs. 15.4%, P